Utilization of TikTok as a Learning Platform in Developing Business Ideas for Housewives in Athya IV Housing Complex, Kayu Putih Street, Simpang Baru, Tampan, Pekanbaru - Bintang Citra Aulia; Mutia Salsabila; Sindi Amelia; Rika Fitri Ramadani (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
At the Athya IV Housing Complex on Jl. Kayu Putih, Simpang Baru, Tampan, Pekanbaru, this study investigated the use of TikTok as a non-formal learning space in the process of developing business ideas for housewives. This study employed a qualitative methodology utilizing in-depth interviews. Informants were purposively selected from housewives who actively use social media, especially TikTok, to seek inspiration and knowledge about productive activities. The results showed that social media, especially TikTok, has become an effective learning resource in encouraging creativity and economic independence for housewives. Housewives can acquire new skills such as making culinary products, understanding how to sell online, and developing business ideas based on household skills by watching short video content. However, several problems exist, including time constraints, difficulty verifying the accuracy of information, and a lack of systematic follow-up content. TikTok can be a good non-formal learning platform for housewives if they have sufficient digital literacy.